Fibroblast Activation Protein Expressing Mesenchymal Cells Promote Glioblastoma Angiogenesis - Balaziova, Eva; Výmola, Petr; Hrabal, Petr; Mateu, Rosana; Zubaľ, Michal; Tomas, Robert; Netuka, David; Kramar, Filip; Zemanova, Zuzana; Svobodova, Karla; Brabec, Marek; Sedo, Aleksi; et al. (Cancers, 2021)
Fibroblast activation protein (FAP) is a membrane-bound protease that is upregulated in a wide range of tumours and viewed as a marker of tumour-promoting stroma. Previously, we demonstrated increased FAP expression in glioblastomas and described its localisation in cancer and stromal cells. In this study, we show that FAP+ stromal cells are mostly localised in the vicinity of activated CD105+ endothelial cells and their quantity positively correlates with glioblastoma vascularisation. FAP+ mesenchymal cells derived from human glioblastomas are non-tumorigenic and mostly lack the cytogenetic aberrations characteristic of glioblastomas. Conditioned media from these cells induce angiogenic sprouting and chemotaxis of endothelial cells and promote migration and growth of glioma cells. In a chorioallantoic membrane assay, co-application of FAP+ mesenchymal cells with glioma cells was associated with enhanced abnormal angiogenesis, as evidenced by an increased number of erythrocytes in vessel-like structures and higher occurrence of haemorrhages. FAP+ mesenchymal cells express proangiogenic factors, but in comparison to normal pericytes exhibit decreased levels of antiangiogenic molecules and an increased Angiopoietin 2/1 ratio. Our results show that FAP+ mesenchymal cells promote angiogenesis and glioma cell migration and growth by paracrine communication and in this manner, they may thus contribute to glioblastoma progression.